A suggested algorithm for detection of multi drug-resistant tuberculosis in Zimbabwe - Beauty Makamure; Salome Makumbirofa; Tsitsi Bandason; Paul Leccese; Reggie Mutetwa; Val Robertson; Peter Mason (Journal of Infection in Developing Countries)
Introduction: Rapid genotypic and phenotypic methods for multi-drug-resistant-tuberculosis (MDR-TB) detection are now widely available. Zimbabwe adopted the use of GeneXpert-MTB/RIF, microscopic-observation-drug-susceptibility-assay (MODS) and Mycobacteria-Growth-Indicator-Tube (MGIT) drug-susceptibility-testing (DST). Data is limited on the ideal combination of use of these methods in resource limited settings.